2017
DOI: 10.1038/srep46151
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophages from ExPEC Reservoirs Kill Pandemic Multidrug-Resistant Strains of Clonal Group ST131 in Animal Models of Bacteremia

Abstract: Multi-drug resistant (MDR) enteric bacteria are of increasing global concern. A clonal group, Escherichia coli sequence type (ST) 131, harbors both MDR and a deadly complement of virulence factors. Patients with an immunocompromised system are at high risk of infections with these E. coli and there is strong epidemiologic evidence that the human intestinal tract, as well as household pets, may be a reservoir. Here, we examine if phages are an effective treatment strategy against this clonal group in murine mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 84 publications
(94 reference statements)
2
62
0
Order By: Relevance
“…First, the efficiency of plating (EOP) score was calculated. The latter is the ratio between the bacteriophage titer obtained with the HG001 strain divided by the titer obtained with the SH50-2 reference strain used for the production of bacteriophages; the closer this score is to 1, the more efficient the bacteriophages are (strong killers, EOP Ͼ 0.1; intermediate killers, 0.005 Ͻ EOP Ͻ 0.09; weak killers, EOP Ͻ 0.005) (32). Second, the growth inhibition of S. aureus by bacteriophages in liquid medium was assessed by culturing bacteria in a 96-well plate at a starting concentration of 10 7 CFU/ml with or without bacteriophages at two concentrations (multiplicity of infection [MOI] of 1 or 10 bacteriophages per bacteria).…”
Section: Methodsmentioning
confidence: 99%
“…First, the efficiency of plating (EOP) score was calculated. The latter is the ratio between the bacteriophage titer obtained with the HG001 strain divided by the titer obtained with the SH50-2 reference strain used for the production of bacteriophages; the closer this score is to 1, the more efficient the bacteriophages are (strong killers, EOP Ͼ 0.1; intermediate killers, 0.005 Ͻ EOP Ͻ 0.09; weak killers, EOP Ͻ 0.005) (32). Second, the growth inhibition of S. aureus by bacteriophages in liquid medium was assessed by culturing bacteria in a 96-well plate at a starting concentration of 10 7 CFU/ml with or without bacteriophages at two concentrations (multiplicity of infection [MOI] of 1 or 10 bacteriophages per bacteria).…”
Section: Methodsmentioning
confidence: 99%
“…These strains readily colonize the human intestine, which can become a reservoir, prior to extraintestinal infection (Nicolas-Chanoine, Bertrand and Madec, 2014). Previous studies reported that phage HP3, a lytic myovirus isolated from environmental reservoirs of ExPEC, could reduce ST131 bacteremia and disease severity in murine models of infection (Green et al, 2017a;Ma et al, 2018). Since the human gastrointestinal tract is the primary reservoir of ExPEC ST131, we wondered if phage HP3 could act prophylactically to reduce or eliminate ExPEC burden in the intestine.…”
Section: The Gastrointestinal Tract Is Prohibitive To Phage Therapymentioning
confidence: 99%
“…Phages HP3, ES12, ES17, ES19, ES21 and ES26 have been previously described and characterized (Green et al, 2017a;Gibson et al, 2019). Phage 6914,6915 and 6939 were recently isolated from sewage.…”
Section: Bacterial Strains and Phagesmentioning
confidence: 99%
“…To understand the range of possible outcomes on a bacterial growth when exposed to both phage and antibiotic, we assessed bacterial growth when exposed to concentrations of antibiotics that blankets the MIC across multiple orders of magnitude of phage titer over time in an optically-based microtiter plate assay system. The primary phage used throughout the investigation, Ф HP3, is a highly effective killer of the ST131 ExPEC clinical isolates and is commonly used as a prototype in the laboratory (24). Since an inoculum effect was observed with this isolate in the presence of different antibiotics ( Fig.…”
Section: Formation Of a Comprehensive Antibiotic-phage Synergy Systemmentioning
confidence: 99%
“…The clinical isolate ExPEC ST131 strain JJ2528 used in this study was kindly provided by Dr. James R. Johnson (56) and the plasmids (pTP123-CTX-M-14 WT and pTP123-CTX-M-14 A77V/D240G) that confer antibiotic resistance were kindly provided by Dr. Timothy Palzkill (25). The phages used in this study, Ф HP3 and Ф ES12, were previously isolated from environmental sources (24,55). All antibiotics were prepared fresh, and filter sterilized (except chloramphenicol and trimethoprim due to solvent used for these antibiotics).…”
Section: Bacterial Culture Plasmids Phage and Antibioticsmentioning
confidence: 99%